PENINGKATAN KETERAMPILAN BERBICARA MELALUI PERMAINAN KOTAK RABA DAN BISIK BERANTAI PADA ANAK USIA 5-6 TAHUN KELAS B1 TK NEGERI PEMBINA KAPUAS HULU - (F54209021), Kusmiati; Ali, Muhamad; ., Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The aim of this research is to obtain information and clarity on improving speaking skills through the game of kotak raba and bisik berantai in children aged 5-6 years. Increased conversation skills in children, among others, can be seen from the child's ability to reveal the Indonesian vocabulary and the ability to convey a message. The method used is descriptive method. The shape of this research study is there a class action research. This study was conducted in two cycles, and each cycle consisted of three meetings with the State took place in TK Negeri Pembina Kapuas Hulu. Research subject is class B1, amounting 30 children and the average age of 5-6 years. Data collection techniques used are direct observation during the learning activities are being carried out. These results indicate that learning to improve speaking skills through the game of kotak raba and bisik berantai in children aged 5-6 years state trustees class B1 TK Negeri Pembina Kapuas Hulu has been successful. It is proved that: 1) Learning Planning using the game of kotak raba and bisik berantai in accordance with the steps that have been determined to improve the ability of children reveal Indonesian vocabulary with category average value of 3.85% in the first cycle and second cycle with category average value of 4.94%; 2) The game of kotak raba and bisik berantai can improve the ability of children reveal Indonesian vocabulary in the first cycle 36.7%, while 76.7% in the second cycle; 3) The game of kotak raba and bisik berantai can improve the child grammar in conveying the message that consists of 4 to 5 with a right in the first cycle of 40%, while 76.7% in the second cycle. Kata kunci : Pendidikan Anak Usia Dini, Keterampilan berbicara